Near-Infrared Autofluorescence Imaging in Thyroid Surgery: A Systematic Review and Meta-Analysis. Issue 9 (15th August 2022) - Lu, Wei; Chen, Qiang; Zhang, Pei; Su, Anping; Zhu, Jingqiang
Abstract: Objective: This meta-analysis aimed to assess the position of near-infrared autofluorescence (NIRAF) imaging in the recognition and protection of the parathyroid gland (PG) during thyroidectomy. Methods: The PubMed, MEDLINE, EMBASE, Web of Science, and Cochrane Library databases were searched up to June 2021. The primary outcome was to evaluate the rates of postoperative hypocalcemia, inadvertent PG resection, and autotransplantation of PG when adopting NIRAF imaging compared with standard naked-eye (N–E) surgery. Results: Eight studies with 2, 889 patients were enrolled in the analysis. Our analysis showed that the incidence of transient hypocalcemia was 7.11% (60/844) in the NIRAF group and 22.40% (458/2045) in the N–E group ( p < 0.0001) and the rate of transient hypoparathyroidism was 28.31% (126/445) and 33.36% (496/1487) in the NIRAF and N–E groups ( p = 0.0008). The rate of inadvertent resection of PGs was 7.65% (55/719) in the NIRAF group and 14.39% (132/917) in the N–E group ( p < 0.0001). No significant difference was observed in other indexes including the pooled proportion of permanent hypocalcemia and rate of PG autotransplantation. Conclusions: The application of NIRAF imaging in thyroidectomy can help lower the incidence of inadvertent PG resection and reduce the risk of postoperative hypocalcemia and hypoparathyroidism compared with N–E recognition.